Temporal dissociation between sodium depletion and sodium appetite appearance: Involvement of inhibitory and stimulatory signals - Margatho, L. O. (2015)
Our aim was to analyze the participation of inhibitory and stimulatory signals in the temporal dissociation between sodium depletion (SD) induced by peritoneal dialysis (PD) and the appearance of sodium appetite (SA), particularly 2. h after PD, when the rats are hypovolemic/natremic but SA is not evident. We investigated the effects of bilateral injections of the serotonin (5-HT) receptor antagonist, methysergide, into the lateral parabrachial nucleus (LPBN) on hypertonic NaCl and water intake 2. h vs. 24. h after PD. We also studied plasma renin activity (PRA) and aldosterone (ALDO) concentration 2. h vs. 24. h after PD. Additionally, we combined the analysis of brain Fos immunoreactivity (Fos-ir) with the detection of double immunoreactivity in 5HT and oxytocinergic (OT) cells 2. h after PD. Bilateral LPBN injections of methysergide (4. μg/200. nl at each site) increased NaCl intake when tested 2. h after PD compared to controls. We found a significant increase in PRA and ALDO concentration after PD but no differences between 2 and 24. h after PD. We also found for the first time a significant increase 2. h after PD in the number of Fos-ir neurons in the brainstem nuclei that have been shown to be involved in the inhibition of SA.In summary, the results show that 5HT-mechanisms in the LPBN modulate sodium intake during the delay of SA when the renin angiotensin aldosterone system (RAAS) is increased. In addition, the activation of brainstem areas previously associated with the satiety phase of SA is in part responsible for the temporal dissociation between SD and behavioral arousal.